Ukraine : 2016 Article IV Consultation and third review under the Extended Arrangement, Requests for a Waiver of Non-Observance of a Performance Criterion, Waiver of Applicability, Rephasing of Access and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2016 Article IV Consultation shows that following a severe crisis in 2014-15, the economy of Ukraine is growing again. The flexible exchange rate and tight fiscal and monetary policies have greatly reduced internal and external imbalances. The current account deficit fell sharply, from more than 9 percent of GDP in 2013 to 3.6 percent of GDP in 2016. The overall fiscal deficit declined to 2.3 percent of GDP in 2016. Growth will remain at 2 percent in 2017 due to the impact of the blockade in the eastern part of Ukraine, but is expected to reach 3 percent in 2018 as the economy adjusts and about 3.5-4.0 percent over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet